Desenvolvimento de sistema biodegradável contendo bevacizumabe para inibição da neovascularização da córnea - Ana Elisa Reis Ferreira (2014)
Ocular neovascularization is the formation of new blood vessels in the tissues of the eye and is involved in nearly all major eye diseases. Corneal neovascularization is a complication that can lead to vision loss and develops in response to inflammation, infections, injuries, surgeries, use of contact lenses, among others. The vascular endothelial growth factor (VEGF) is one of the most important factors involved in corneal neovascularization. For this reason, the use of VEGFs inhibitors is on the rise. Among these, bevacizumab, an anti-VEGF monoclonal antibody that binds all isoforms of VEGF-A, has shown great efficacy in the treatment of neovascularization, including that of the cornea. The topical application of medicines is the desired treatment for diseases in the anterior segment of the eye; however, repeated administrations and high concentrations of the drug are necessary. As an alternative to these difficulties, extended-release systems are being studied. Therefore, in this work a biodegradable release system was developed, characterized, and evaluated consisting of polyurethane derived from poly (å-caprolactone) containing bevacizumab for topical use. An aqueous polyurethane dispersion containing bevacizumab was produced, submitted to a lyophilization process, and compressed. The system was characterized and evaluated by scanning electron microscopy, thermal analysis, and Fourier transform infrared spectroscopy. Moreover, release studies, in vitro degradation and toxicity, and the evaluation of antiangiogenic activity using chick embryo chorioallantoic membrane and rabbit cornea were performed. In the evaluated models, the use of bevacizumab (Avastin®) and the bevacizumab-loaded polyurethane device led to similar results regarding neovascularization inhibition. In the chorioallantoic membrane model, the bevacizumab-loaded polyurethane device reduced angiogenesis by 50.27% when compared to the negative control group. In the rabbit model of corneal neovascularization, the mean density of vessels/field was reduced by 46.87% considering Factor VIII immunohistochemistry picture analysis in the bevacizumab-loaded polyurethane device group as compared to the negative control sections. In both models, no significant difference could be identified between the bevacizumab-loaded polyurethane device and the positive control group, leading to similar results regarding neovascularization inhibition. The results show that it was possible to obtain a release system containing bevacizumab through reproducible methods that provide the drug in its biologically active form. Although the system still needs adjustments, such as increasing the release time, it can be considered promising for the incorporation of drugs that need special care in the preparation of systems, such as low temperatures, mild shaking, and the absence of organic solvents.